A Catheter-Based Suture-Free Approach to Bilioenteric Anastomosis: A Pilot Study. (April 2013) - Seal, John B.; Stern, Jordan R.; VanHa, Thuong; Alverdy, John C.; Testa, Giuliano
Bilioenteric anastomoses are commonly performed during liver transplantation, reconstruction following tumor resection, and repair of bile duct injury. Ischemia plays an important role in both short- and long-term complications related to biliary anastomoses. The authors describe a catheter-based, suture-free approach to bilioenteric anastomosis that aims to reduce or eliminate tissue trauma and foreign material that contribute to anastomotic ischemia. The device uses a novel "umbrella" anchoring mechanism to approximate bowel to the transected bile duct over a percutaneously placed transhepatic catheter. The authors performed an open choledochojejunostomy using the device in 7 pigs. The anastomosis was assessed with cholangiography, gross inspection, and histology at the time of necropsy. The procedure was well tolerated, with no evidence of anastomotic leak in any of the study animals. This alternative catheter-based approach to bilioenteric anastomoses is safe and effective, offers potential advantages over traditional approaches, and can be easily adapted to a minimal access surgery.